Outcomes of a complementary and alternative medicine based on vitamins, herbal products, and amino acid as a first line treatment in idiopathic overactive bladder syndrome in men and women without bladder outlet obstruction - Morselli, Simone; Gemma, Luca; Liaci, Andrea; Campi, Riccardo; Serni, Sergio; Li Marzi, Vincenzo (Urologia, 2022)
To evaluate the efficacy and tolerability of a complementary and alternative medicine (CAM) called Kubiker (Naturmed, Montegranaro, FM, Italy), consisting of vitamins (C and D), herbal products (cucurbita maxima, capsicum annum, polygonum cuspidatum), and amino acid L-Glutamine, as first line treatment of (OAB). According to institutional protocols, data on patients addressing to a tertiary referral centre for OAB symptoms were recorded. OAB was evaluated through validated questionnaires including ICIQ-SF, USS, and OAB-q-SF. Patients with previous antimuscarinic or β3 agonist treatment, neurological disease or pathologies which may mimic OAB, including infections, were excluded. Only unobstructed patients were considered and were given CAM twice daily for 12 weeks. After treatment, symptoms were re-evaluated repeating previous questionnaires and PGI-I was given to evaluate perceived improvement. A total of 41 patients were evaluated and 35 respected inclusion criteria and were enrolled. All subjects had a full compliance and adherence with CAM medication intake. The median patient's age was 65 (56-73). Male were 8 (22.9%) while females were 27 (77.1%). Median baseline OAB-q SF and ICIQ-SF scores were 18 (15-25) and 9 (6-13), respectively. After treatment, 85.7% patients had a clinical benefit, with a significant reduction of OAB symptoms, also according to USS ( < 0.01). The median OAB-q SF and ICIQ-SF scores were 10 (7-15) and 6 (0-8) ( < 0.01). CAM was successful with an improvement in subjective patient's satisfaction, with a median PGI-I score of 2 (1-3). Patients (men and women) who still had UUI after 3 months CAM medication were eight (22.8%), and among them, those who did not refer any therapeutic benefit were five (14.3%). According to our study, CAM may be useful medication for a first line treatment of uncomplicated idiopathic OAB cases, providing a nonnegligible effects on symptoms. However, further studies are mandatory to draw definitive conclusions.